1998
DOI: 10.1104/pp.116.2.805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Role for an Azide-Sensitive Factor in the Thylakoid Transport of the 17-Kilodalton Subunit of the Photosynthetic Oxygen-Evolving Complex1

Abstract: We have examined the transport of the precursor of the 17-kD subunit of the photosynthetic O 2 -evolving complex (OE17) in intact chloroplasts in the presence of inhibitors that block two proteintranslocation pathways in the thylakoid membrane. This precursor uses the transmembrane pH gradient-dependent pathway into the thylakoid lumen, and its transport across the thylakoid membrane is thought to be independent of ATP and the chloroplast SecA homolog, cpSecA. We unexpectedly found that azide, widely considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Thus, the reactions were performed in long microfuge tubes with three layers: the transport reaction at the top, a layer of insulating silicone oil in the middle (Hurwitz et al. , 1965; Leheny et al. , 1998), and a bottom layer containing 20% TCA (transport and binding assays) or 2 × IB (chase assays).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reactions were performed in long microfuge tubes with three layers: the transport reaction at the top, a layer of insulating silicone oil in the middle (Hurwitz et al. , 1965; Leheny et al. , 1998), and a bottom layer containing 20% TCA (transport and binding assays) or 2 × IB (chase assays).…”
Section: Resultsmentioning
confidence: 99%
“…DnaK, GroEL) and proteases (e.g. ClpXP, FtsH) play an important role in the early stages of Tat targeting and translocation in bacteria 25,36,38,39,45 and plants [55][56][57][58] (for a review see Fisher and DeLisa 34 ). Accordingly, we tested a panel of E. coli mutant strains lacking well-characterized chaperones or proteases and found that the molecular chaperone DnaK exerted the most significant effect on the expression and transport of synthetic Tat substrates such as ssTorA-GFP-SsrA, ssTorA-GFP and ssTorA-MBP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that import of Tat proteins takes place even when the trans ‐thylakoid ΔpH is depleted (Di Cola et al 2005a, Finazzi et al 2003), limits the use of nigericin as a pathway‐specific inhibitor. Azide was shown to inhibit the import of OE17, a Tat pathway protein, but unlike pPPO the effect was seen only after pOE17 import was inhibited by nigericin (Leheny et al 1998).…”
Section: Discussionmentioning
confidence: 99%